Prediction and Optimization of Rheological Parameters of Potato Starch Modified by Cold Plasma - Ali Taghavi; Azadeh Ranjbar Nedamani; Ali motevali; Hashemi Seyyed Jafar (فناوری‌های جدید در صنعت غذا)
In this study, potato starch was treated with cold plasma and then dried at different temperatures. Cold plasma was generated using a plasma reactor with copper and steel electrodes, a voltage of 20 kV, a current of 3 mA, and a frequency of 50 Hz, using atmospheric air, and was applied to the sample. The flow behavior of 2% starch dispersion was then fitted with rheological models including the power law, Herschel-Bulkley, and Casson models using the regression toolbox of SPSS 20 software. The results showed that the choice of the appropriate rheological model depends on the type of treatment. However, the Herschel-Bulkley model provided a more accurate fit with the data in most cases. With an increase in pre-gelatinization temperature, the final viscosity of the starch samples decreased. The n coefficient in samples that were not pre-gelatinized increased with other factors, but in samples pre-treated at 55°C, it decreased with other factors. Drying temperature generally reduced the viscosity of the samples. However, at each temperature, the effect of pre-gelatinization temperature and cold plasma treatment time on viscosity changes was significant. Coefficients such as k and n also decreased with increasing drying temperature. Increasing the cold plasma treatment time reduced the viscosity and k in the samples but showed significant fluctuations in the value of n. In samples that received the longest cold plasma treatment time of 30 minutes, increasing the drying and pre-gelatinization temperatures reduced n and changed the fluid behavior from nearly Newtonian to shear-thinning. The findings of this study not only provide a better understanding of the rheological behavior of starch but also offer strategies for optimizing industrial processes related to the production and application of this type of starch.